Engineering Rhizobial Bioinoculants: A Strategy to Improve Iron Nutrition - S. J. Geetha; Sanket J. Joshi (The Scientific World Journal)
Under field conditions, inoculated rhizobial strains are at a survival disadvantage as compared to indigenous strains. In order to out-compete native rhizobia it is not only important to develop strong nodulation efficiency but also increase their competence in the soil and rhizosphere. Competitive survival of the inoculated strain may be improved by employing strain selection and by genetic engineering of superior nitrogen fixing strains. Iron sufficiency is an important factor determining the survival and nodulation by rhizobia in soil. Siderophores, a class of ferric specific ligands that are involved in receptor specific iron transport into bacteria, constitute an important part of iron acquisition systems in rhizobia and have been shown to play a role in symbiosis as well as in saprophytic survival. Soils predominantly have iron bound to hydroxamate siderophores, a pool that is largely unavailable to catecholate-utilizing rhizobia. Outer membrane receptors for uptake of ferric hydroxamates include FhuA and FegA which are specific for ferrichrome siderophore. Increase in nodule occupancy and enhanced plant growth of the fegA and fhuA expressing engineered bioinoculants rhizobial strain have been reported. Engineering rhizobia for developing effective bioinoculants with improved ability to utilize heterologous siderophores could provide them with better iron acquisition ability and consequently, rhizospheric stability.